A novel phenotype associated with the R162W variant in the KCNJ13 gene. (4th July 2022) - Schroeder, Marion; Peter, Virginie G.; Gränse, Lotta; Andréasson, Sten; Rivolta, Carlo; Kjellström, Ulrika
ABSTRACT: Background: Pathogenic variants in KCNJ1 3 have been associated with both autosomal dominant Snowflake vitreoretinal degeneration (SVD) and autosomal recessive Leber congenital amaurosis. SVD is characterized by aberrant vitreoretinal interface leading to increased risk of retinal detachment, crystalline retinal snowflake deposits, optic disc abnormalities, early-onset cataract, and cornea guttae. Reduced dark adaptation and reduced scotopic rod b-waves have also been described. We report a novel phenotype associated with the R162W variant in KCNJ13 . Methods: Four affected members of a Swedish family were included. Three of them were examined with best corrected visual acuity, Goldmann perimetry, full-field—and multifocal electroretinography, optical coherence tomography, fundus color photographs, fundus autofluorescence images, slit lamp inspection, and genetic testing. The fourth subject only managed genetic testing. Results: All subjects carry the pathogenic missense variant; c.484C>T (NM_002242.4), R162W, in KCNJ13 . ERG measurements revealed reduced macular—as well as general retinal function. Two of the subjects had a history of retinal detachment and the two younger subjects demonstrated early onset cataract. They all had structural macular changes and slightly gliotic optic discs. Conclusion: In this family, the R162W variant in KCNJ13, previously described in association with SVD, causes a somewhat novel phenotype including macular dystrophy and moderate reduction of general retinal function as the main features combined with disc abnormalities, retinal detachment, and presenile cataract that has been described before. In times of up-coming gene-based therapies, it is important to report new genotype—phenotype associations to improve the possibilities to identify future treatment candidates.